Resilient-Based Posyandu for Flood Disaster in Benua Raya Village, South Kalimantan: Posyandu Berbasis Tangguh Bencana Banjir Di Desa Benua Raya Kalimantan Selatan - Varinia Pura Damayanti; Muhammad Alif (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The public's understanding and knowledge of disasters are lacking, moreover, the territory of the State of Indonesia has a high potential for disasters to occur. South Kalimantan is one of the provinces that often experience disasters, especially floods and land and forest fires. Posyandu is a community group that has great potential in disseminating disaster information, the role of posyandu cadres is important in health activities. This community service activity is carried out to increase the knowledge, attitudes, and skills of Posyandu cadres when a disaster occurs, especially a flood disaster. The method used is to conduct education, outreach, demonstrations, and simulations. The activities carried out were the socialization of the role of posyandu cadres during a disaster, training on making complementary foods during a disaster, disaster simulations, and flood evacuation simulations for posyandu cadres. Posyandu cadres the participants can understand and know the role of cadres in disaster and can practice all the training carried out.